Regional Protocol Roles in Local Government Social Conduct Management: Peran Protokol Regional dalam Pengelolaan Perilaku Sosial di Pemerintahan Daerah - Purwati, Umi Wahyu; Agustina , Isna Fitria (Indonesian Journal of Public Policy Review, 2025)
General Background: Protocol management plays a crucial role in maintaining order, dignity, and professionalism in local government activities. Specific Background: In Sidoarjo Regency, the Protocol and Leadership Communication Division serves as the key coordinator ensuring that official interactions align with administrative norms and leadership ethics. However, the growing complexity of official engagements exposes gaps in coordination, documentation, and digital system integration. Knowledge Gap: Despite its strategic role, limited research explores how regional protocol functions influence the quality of social conduct governance within local administrations. Aims: This study analyzes how the regional leaders’ protocol supports structured, dignified, and effective social conduct implementation. Results: Using a descriptive qualitative approach, findings show that effective protocol management relies on compliance with regulations, stakeholder coordination, and leadership professionalism, supported by Standard Operating Procedures (SOPs) but constrained by limited human resources and digital readiness. Novelty: The study introduces an integrated model of protocol governance combining professionalism, coordination, and digital transformation. Implications: Strengthening protocol systems enhances institutional credibility and contributes to modern public service governance at the regional level. Highlights: Establishes an integrated protocol governance model. Identifies digitalization as a key improvement area. Reinforces protocol’s strategic role in public credibility. Keywords: Protocol Governance, Local Leadership, Social Conduct, Coordination, Public Administration